Lipopolysaccharide Derived From the Lymphoid-Resident Commensal Bacteria Alcaligenes faecalis Functions as an Effective Nasal Adjuvant to Augment IgA Antibody and Th17 Cell Responses - Wang, Yunru; Hosomi, Koji; Shimoyama, Atsushi; Yoshii, Ken; Nagatake, Takahiro; Fujimoto, Yukari; Kiyono, Hiroshi; Fukase, Koichi; Kunisawa, Jun (Frontiers in Immunology, 2021)
Alcaligenes spp., including A. faecalis, is a gram-negative facultative bacterium uniquely residing inside the Peyer’s patches. We previously showed that A. faecalis-derived lipopolysaccharides (Alcaligenes LPS) acts as a weak agonist of toll-like receptor 4 to activate dendritic cells and shows adjuvant activity by enhancing IgG and Th17 responses to systemic vaccination. Here, we examined the efficacy of Alcaligenes LPS as a nasal vaccine adjuvant. Nasal immunization with ovalbumin (OVA) plus Alcaligenes LPS induced follicular T helper cells and germinal center formation in the nasopharynx-associated lymphoid tissue (NALT) and cervical lymph nodes (CLNs), and consequently enhanced OVA-specific IgA and IgG responses in the respiratory tract and serum. In addition, nasal immunization with OVA plus Alcaligenes LPS induced OVA-specific T cells producing IL-17 and/or IL-10, whereas nasal immunization with OVA plus cholera toxin (CT) induced OVA-specific T cells producing IFN-γ and IL-17, which are recognized as pathogenic type of Th17 cells. In addition, CT, but not Alcaligenes LPS, promoted the production of TNF-α and IL-5 by T cells. Nasal immunization with OVA plus CT, but not Alcaligenes LPS, led to increased numbers of neutrophils and eosinophils in the nasal cavity. Together, these findings indicate the benign nature of Alcaligenes LPS is an effective nasal vaccine adjuvant that induces antigen-specific mucosal and systemic immune responses without activation of inflammatory cascade after nasal administration.